2019
DOI: 10.1002/ejoc.201901303
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Green Synthesis of Functionalized Phenols from Aromatic Boronic Compounds

Abstract: Phenol and its derivatives are fundamental building blocks in organic synthesis and materials science. Over the past decades, tremendous attention has been paid to construct functionalized phenols, and various methods have been developed. Owing to the high efficiency and mild reaction conditions, synthesis of phenols from the hydroxylation of aryl boronic compounds has been emerging as a promising approach. In this review, we summarize the progress using aryl boronic compounds as starting reagents to synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 103 publications
0
25
0
1
Order By: Relevance
“…During PNRSS, H 2 O 2 initially reacts reversibly with the PBA, generating positive going spiky events, likely resulting from an intermediate state prior to the production of a phenol (Fig. 4a(ii)) as proposed in literatures 60,61 . However, the boron atom is not yet removed at this stage.…”
Section: Resultsmentioning
confidence: 76%
“…During PNRSS, H 2 O 2 initially reacts reversibly with the PBA, generating positive going spiky events, likely resulting from an intermediate state prior to the production of a phenol (Fig. 4a(ii)) as proposed in literatures 60,61 . However, the boron atom is not yet removed at this stage.…”
Section: Resultsmentioning
confidence: 76%
“…A series of radical scavengers such as TEMPO, benzoquinone, BHT, and DABCO was used in this study and resulted in the respective phenol formation (Figure 3A). The study indicated that the reaction does not involve any possible hydrogen peroxide radicals, such as hydroxyl radical, peroxy hydroxyl radical, and superoxide radical [34] . A plausible mechanism for the reaction has been proposed based on the previously reported literature [32] .…”
Section: Figurementioning
confidence: 77%
“…A plausible mechanism for the reaction has been proposed based on the previously reported literature [32] . The transformation of boronic acid II to phenol V was accelerated rapidly by forming boronic acid adduct III with activated hydrogen peroxide complex I , which further undergoes rearrangement to give intermediate compound IV and final hydrolysis yielded phenol V (see Supporting information, Figure S1) [34] …”
Section: Figurementioning
confidence: 87%
“…The development of effective protocols for the preparation of functionalized phenols significantly impacts modern chemical science. Although various approaches have been developed starting from assorted molecules, such as the aryl halides, 3 benzyne, 4 aromatic boronic acids, 5 through C–H activation, 6–8 and diazonium salts, 9 there is still a challenge to make this process more efficient. 10–12 Among these methods, due to the simplicity and availability of aryl halides, metal-catalyzed hydroxylation of aryl halides is the most favorable reaction for the synthesis of phenol derivatives.…”
Section: Introductionmentioning
confidence: 99%